Chapter 11 Care in the Cage Materializing Moral Economies of Animal Care in the Biomedical Sciences, c.1945- - Kirk, Robert G W (Taylor & Francis, 2016)
This chapter adopts a historical perspective to explore how material infrastructures have structured human-animal relationships within the biomedical "animal house," c.1945 to the present. It argues material infrastructures serve to structure the multiple values that have informed and shaped human-animal relations within the experimental biomedical sciences. By exploring how multispecies sociocultural relations performatively shape and are shaped by the physical infrastructures that make up lived relations and shared labor in the animal house and laboratory, the chapter charts how "multispecies relations" form a dynamic, situated and emergent "moral economy" wherein the moral economy cannot be separated from factors that would properly be associated with a political economy of animal-dependent experimental science.